Latin America and the Caribbean and the European Union : striving for a renewed partnership - Rosales, Osvaldo (UN ECLAC SantiagoCL, 2012)
Provides an updated analysis of trade, investment and cooperation relations between Latin America and the Caribbean and the European Union, preparatory to the 7th European Union-Latin America Summit, Santiago, Chile in 2012.